The idea of love [large type] - Henry, Patti Callahan (Wheeler Publishing, 2015)
Ella is young, beautiful, and deeply in love -- until her husband dies in a tragic sailing accident while trying to save her. Or so she'll have everyone believe. Screenwriter Hunter needs a hit. He's on the look-out for a love story. It doesn't matter who it belongs to. So when Hunter and Ella meet in Watersend, South Carolina, it feels like something close to fate.